RANCANG BANGUN JARINGAN WI-FI UNTUK KOMUNIKASI DARING DI DESA TENJOLAYA - Yuli Kurnia Ningsih; Nazmia Kurniawati (P3M Politeknik Negeri Indramayu, 2020)
The availability of telecommunication infrastructure affects the development of an area, especially areas that have the potential for tourism and agricultural products such as Tenjolaya Village. The development of RT RW net as internet network infrastructure using Wi-Fi technology can be a supporting sector for the economic development of the village. Network deployment is carried out in three stages: preparation, construction and measurement. In the preparation stage, the number of users is calculated and a survey of the installation location is carried out. Furthermore, network development is carried out based on the network architecture that has been designed with CPE totaling four points. In the final stage, four parameters are measured to check the network conditions. The parameters are throughput, signal strength, CCQ, and SNR. From the measurement results, the measured throughput at the access point has a value range of 17 to 30 dBm. The measured Tx signal strength has a value of -75 to -39 dBm while the Rx signal strength is between -72 to -37 dBm. The CCQ value is between 76 and 100%. The measured SNR parameter has a value of 38 to 77 dBm.